PENGARUH SIKAP, NORMA SUBYEKTIF, DAN MINAT TERHADAP KEPUTUSAN PEMBELIAN PADA PEDAGANG UMKM CAMILAN PISANG KEJU S3 DI YOGYAKARTA - Muhammad Baladil Amin; Uju Suji’ah (Bajang Institute, 2023)
The research aims to determine the relationship between attitudes, subjective norms, interests and purchasing decisions as measured by partial significance tests (t tests) and simultaneous significance tests (F tests), data analysis techniques used to answer hypotheses using multiple linear regression tests. The population of this research is all consumers in the Special Region of Yogyakarta. The sampling technique used a purposive sampling method with the criteria of consumers who had purchased S3 banana cheese snacks, with a sample of 102 people. The research results show that the attitude variable partially has a significant effect, the subjective norm variable partially has an insignificant effect, variables of interest partially have the strongest significant influence on purchasing decisions; Attitude variables, subjective norms, interests simultaneously have a significant effect on purchasing decisions. The results of this research can be a basis for consideration for companies to ensure consumers' attitudes, subjective norms and interests so that they become loyal customers